Adoption of Strategic Alliances by Shoes Industries of the Vale do Rio dos Sinos-RS and Franca-SP clusters: an exploratory study - Gianisella, René Luiza Gastoldi; Souza, Marcos Antonio de; Almeida, Lauro Brito de (Review of Business Management, 2008)
The new environment of the companies, result of the relative opening of the market caused by the globalization has set a new challenge to assure the continuity of the businesses. Competitive strategies have been implemented aiming to overcome such challenge and, amongst them, strategic alliances have shown to be a viable alternative. In this context, this article has as objective to investigate the degree of use of strategic alliances by the medium and large companies of the shoes industries located in clusters of Vale do Rio dos Sinos (RS) and Franca (SP). This exploratory and descriptive research had the participation of 54 companies, being 33 from Vale do Rio dos Sinos and 21 from Franca, which answered a questionnaire with closed questions. The analysis of the data was given through descriptive statistics. Main conclusions, follow as: (1) the majority of the companies have joint activities; (2) the companies are nearer to alliances that do business than to the strategic ones; (3) alliances with competitors are inexpressive - suppliers and customers predominate; (4) the control of alliances result is insufficient; (5) trust and adequate partner are determinative factors. Key-words: Competitive strategies. Strategic alliances. Shoes industries cluster.